BUILDING MENTAL HEALTH SYSTEMS IN LAMPUNG: LESSONS FROM DATA AND PRACTICE: BUILDING MENTAL HEALTH SYSTEMS IN LAMPUNG: LESSONS FROM DATA AND PRACTICE - Suri, Nurma; Ayu SWP, Fadillah (JFL : Jurnal Farmasi Lampung, 2025)
Mental disorders are the result of a long and complex psychosocial development process, influenced by family factors, the environment, and individual social conditions. Data from the 2007-2018 Riskesdas and the 2023 Indonesian Health Survey (IHS) show fluctuations in the prevalence of mental disorders in Indonesia, including in Lampung Province. Schizophrenia as a severe mental disorder and mental emotional disorders such as stress, anxiety, and depression are still major problems. Major challenges also arise in the form of the widespread practice of shackling and low access to mental health services. Although the coverage of administrative services is quite high, the quality of services and the success of long-term rehabilitation are not optimal. Low public literacy, lack of health resources, and limited facilities are significant obstacles. The integration of the Mental Health Law into the Health Law No. 17 of 2023 is expected to become a legal umbrella that strengthens an inclusive and sustainable mental health service system. Handling mental disorders needs to involve a cross-sectoral approach that is not only curative, but also promotive and preventive, to ensure the recovery of social functions and the overall quality of life of patients. Family support, community support, and a strong health system are key in tackling the burden of mental disorders in Indonesia. Keywords: Anxiety, Depression, Lampung, Mental Disorders, Schizophrenia